Reservas Particulares do Patrimônio Natural (RPPNs) de Alagoas: da gênese aos usos - Ferreira, Tarciéri de Souza (2022)
Several sectors of society demand essential natural resources to maintain life, so the balance between the use and replacement of these resources is essential. In this context, the creation of protected areas can work as an excellent instrument of environmental management, especially in the provision of ecosystem services. Private Natural Heritage Reserves are private conservation units with the objective of achieving these assumptions. The objective of this study is to understand and characterize the processes related to creation and the uses given to this typology of protected area in Alagoas. A survey of data (spatial, bibliographic, documentary and interviews) was carried out on the reserves. Information from interviews with representatives of public agencies and civil society responsible for the creation and implementation, in addition to the owners or managers of the reserves, was analyzed. With this, we sought to identify three main points: 1. History of creation of RPPNs; 2. Description of the reserves, with administrative and maintenance aspects, conservation, biodiversity, threats; 3. Public and private uses of the reserve. As a result, we hope to assist in the composition of scientific information about them, once the existence of gaps in freely accessible data in official electronic addresses has been identified. As for the partial results obtained so far, it is possible to observe the identification of all the seventy-six existing reserves in the state, as well as the classification by domains and by stages of creation. From this, a higher concentration of reserves was identified in the Atlantic Forest domain compared to the Caatinga domain. This abundance of reserves, mainly in the Atlantic Forest, may be linked to actions by several sectors: the public ministry, the state environmental agency, non-governmental organizations active in this biome, as well as the initiative of the agro-industrial sector, since several protected areas are owned by the sugar and ethanol industries. Therefore, the emergence of RPPNs in the state of Alagoas was motivated by factors such as the institution of SNUC itself; the incentive to landowners through environmental compensation, in the form of a suggestion in accordance with the IMA and MP; regularization through decree 3050/2006; the need for forested areas to implement projects for the reintroduction of endangered species and actions to publicize this type of reserve among landowners carried out by IPMA. All these factors added to the development of the Mais RPPNs, Pró-Reservas plans and all the effort made by the NGOs, as well as a good relationship between the actors involved to facilitate the reduction of bureaucracy in the processes in public agencies were essential for the installation of RPPNs in the state.